Tongue Twister Rap: Bringing Joy to EFL Pronunciation Class - Nizar Indra Mu'thi; Rohmani Nur Indah (English Language in Focus (ELIF), 2021)
This study aims to determine the new combination of tongue twisters with rap music applied in the pronunciation class. The data in this study used a descriptive qualitative approach. The primary data in this study were interviews, documentation, and interview results, which contained pronunciation-learning activities using, rap music. The result of the research is that the application of tongue twister rap in the pronunciation class has several steps are the first is to explain the pronunciation learning material first. The second step is to write a tongue twister on the board and continue by explaining how to read and pronounce it. Then teacher drills the students back slowly until quickly, combining the tongue twister with rap music several times, and guiding the students to practice tongue twister rap as well as making battle rap. The benefits of this application are making pronunciation and speaking more fluent, making pronunciation learning interesting and fun so that it makes students easier to understand learning material, making pronunciation clearer and more correct. The weakness of the application of tongue twister rap is that tongue twister rap can break the concentration of other class students because students are very interested in learning pronunciation due to learning with tongue twister rap. The conclusion is that tongue twister rap is an enjoyable learning technique in pronunciation class. This study suggests continuing research to get information about the effectiveness of tongue twister rap in pronunciation class and find various other techniques in teaching pronunciation.